Estrategias de marketing digital y su repercusión en los emprendimientos del cantón pichincha año 2023- 2024 - Vera Basurto, Josselyn Jamileth (2025)
This research analyzes digital marketing strategies and their impact on businesses in the Pichincha canton during 2024, focusing specifically on clothing retail stores. In an environment marked by increasing digitalization, it is essential to understand the challenges entrepreneurs face in adopting digital tools and their impact on the competitiveness, customer satisfaction, visibility, and sustainability of their businesses. The study was conducted using a mixed approach (qualitative and quantitative), employing inductive, deductive, and descriptive methods. An interview was conducted with the head of the Department of Social and Productive Development of the Decentralized Autonomous Government of the Pichincha Canton. Surveys were also conducted with 100 entrepreneurs and 377 customer surveys. This allowed us to identify the challenges entrepreneurs face, key factors such as loyalty, brand positioning, sales growth, and customer perceptions of the effectiveness of digital marketing. The results show that, although many entrepreneurs use social media platforms like Facebook, Instagram, WhatsApp, and TikTok to promote their products, there is a lack of structured planning and limited use of tools such as paid campaigns or websites. Furthermore, a gap was identified between digital marketing knowledge and its practical application. This work seeks to contribute to academic and practical knowledge about the strategic use of digital marketing in local businesses, offering recommendations to strengthen their competitiveness and contribute to the economic development of the Pichincha canton.